ENTREPRENEURIAL CHARACTERISTICS ARE VIEWED FROM SELF EFFICACY FOR ENTREPREUNEURS IN HARAPAN ISLAND - Kania Ratnasari (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2020)
The purpose of this study was to determine the profile of entrepreneurs in Harapan Island, then to find out the entrepreneurial characteristics and self-efficacy of business actors in Harapan Island. The distribution of questionnaires on entrepreneurial characteristics and self-efficacy was given to 40 entrepreneurs on Harapan Island. The data analysis used is quantitative descriptive analysis, Tabulation Data, Data Display and Conclusion Drawing. The results of this study are the majority of women entrepreneurs aged 44-50 years with an educational background, namely junior high. Then, the overall entrepreneurial characteristics included in the high category with the highest indicator, Need for Achievement and the lowest indicator, Propensity to Take Risk. As for overall self-efficacy, it is categorized as very high with the highest indicator being Strength and the lowest indicator being Generality.